The effect of economic variables over a biodiesel production plant - Marchetti, Jorge Mario (2011)
Biodiesel appears as one of the possible alternative renewable fuels to substitute diesel fuel derived from petroleum. Several researches have been done on the technical aspects of biodiesel production in an attempt to develop a better and cleaner alternative to the conventional process. Economic studies have been carried out to have a better understanding of the high costs and benefits of different technologies in the biodiesel industry. In this work it is studied the effect of the most important economic variables of a biodiesel production process over the general economy of a conventional plant which employs sodium methoxide as catalyst. It has been analyzed the effect of the oil price, the amount of free fatty acid, the biodiesel price, the cost of the glycerin, the effect due to the modification on the methanol price, the washing water price, and several others. Small variations on some of the major market variables would produce significant effects over the global economy of the plant, making it non profitable in some cases. © 2011 Elsevier Ltd. All rights reserved.